Protein composition and bread volume of German common wheat landraces grown under organic conditions - Nora Jahn; Ulla Konradl; Klaus Fleissner; Sabrina Geisslitz; Katharina A. Scherf (Current Research in Food Science)
Landraces are genetically heterogeneous plant populations that are regionally particularly well adapted to the natural and cultural agricultural environment. Their genetic memory originates from pre-industrial agriculture and food production with consequences for their agronomic and processing performance. Since wheat-related disorders have increased in the population, breeding might have resulted in changes in the protein composition. The aim of this study was to investigate the protein composition and baking quality of 14 German common wheat landraces. Six modern varieties served as a control group. The protein composition was determined using modified Osborne fractionation and reversed-phase high-performance liquid chromatography. In addition, the water absorption and bread volume were determined.The crude protein content, proportions of albumins and globulins, water absorption and bread volume did not differ between modern varieties and landraces. The proportion of gliadins was higher in landraces (64.0%) compared to modern varieties (57.6%), whereas the proportion of glutenins was lower in landraces (17.4%) than in modern varieties (22.0%). The same observation was made for the respective gluten protein types except the proportion of ω1,2-gliadins, where there was no difference between the two groups. This resulted in a significantly higher ratio of gliadins to glutenins of 4.3 in landraces compared to 2.8 in the modern varieties, but no difference in the total gluten proportion. Taken together, there was no clear distinction between landraces and modern varieties. However, a few landraces such as Roter Sächsischer Landweizen showed similar characteristics to modern varieties and are therefore interesting for further investigations.